Functionality and Effectiveness Analysis of BJP and INC Websites - Pandey, Neha; Singh, Dev Vrat (Journal of Advanced Research in Journalism & Mass Communication, 2019)
The purpose of this study was to discover the relevance of websites as a tool used by BJP and INC political parties of India in the present scenario when web 2.0 has overshadowed all the other platforms to engage with public. The study selects period of non-election period, i.e., routine politics to assess party’s normal behavior, outside of the obsession of an election campaign. The data for the analysis were collected during the last week of December 2018. During this period, no election campaign was going on. The findings of the data focus on two important aspects of political communication through websites, i.e., Information flow which includes information provision, resource generation, campaigning, networking and participation; and site delivery which includes navigability, visibility, multimedia, accessibility and responsiveness. Further, the researcher also tries to examine the popularity of the website through monthly page views, link analysis and geographic distribution. Using Alexa Way back Machine, the researcher compares the present view of parties’ website with its earlier view. The results suggest that web-based communication is mostly party-initiated top-down and one-way approach. How to cite this article: Pandey N, Singh DV. Functionality and Effectiveness Analysis of BJP and INC Websites. J Adv Res Jrnl Mass Comm 2019; 6(1): 5-15.